2019
DOI: 10.1038/s41586-019-1778-y
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin structure dynamics during the mitosis-to-G1 phase transition

Abstract: Higher-order chromatin organization such as A/B compartments, TADs, and chromatin loops are temporarily disrupted during mitosis 1,2. Since these structures are thought to influence gene regulation, it is important to understand how they are re-established after mitosis. We examined the dynamics of chromosome reorganization by Hi-C after mitosis in highly purified, synchronous cell populations. We observed rapid establishment, gradual intensification, and expansion of A/B compartments. Contact domains form fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
270
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(301 citation statements)
references
References 28 publications
26
270
3
2
Order By: Relevance
“…Principle Component Analysis (PCA) confirmed consistency between our Hi-C replicates and indicated gradual changes in the course of mitotic release ( Figure S5A). Consistent with previous studies (Abramo et al, 2019;Gibcus et al, 2018;Nagano et al, 2017;Naumova et al, 2013;Zhang et al, 2019), we observed a dramatic alteration of chromatin architecture during mitosis ( Figure S5B) with an almost complete loss of compartmentalization, topologically-associating domains (TADs), and specific, longrange interactions ( Figure 5A).…”
Section: Chromosomal Compartments and Domain Boundaries Are Establishsupporting
confidence: 92%
See 1 more Smart Citation
“…Principle Component Analysis (PCA) confirmed consistency between our Hi-C replicates and indicated gradual changes in the course of mitotic release ( Figure S5A). Consistent with previous studies (Abramo et al, 2019;Gibcus et al, 2018;Nagano et al, 2017;Naumova et al, 2013;Zhang et al, 2019), we observed a dramatic alteration of chromatin architecture during mitosis ( Figure S5B) with an almost complete loss of compartmentalization, topologically-associating domains (TADs), and specific, longrange interactions ( Figure 5A).…”
Section: Chromosomal Compartments and Domain Boundaries Are Establishsupporting
confidence: 92%
“…Previous work in human and mouse cell lines has started to dissect the 3D chromatin reorganization during the cell cycle and described distinct models of mitotic or interphase chromosome folding (Gibcus et al, 2018;Liang et al, 2015b;Naumova et al, 2013;Ou et al, 2017) as well as dynamic reorganization during mitotic exit (Abramo et al, 2019;Dileep et al, 2015;Nagano et al, 2017;Zhang et al, 2019). Unrelated studies have reported distinct waves of transcriptional reactivation during mitotic release and a global, transient spike in transcription during G1 entry (Hsiung et al, 2016;Palozola et al, 2017).…”
mentioning
confidence: 99%
“…in daughter cells shortly after NSC mitosis. This is reminiscent of embryonic stem cell differentiation that is also thought to occur in G1 (37,38), especially early G1 at a stage most favorable to massive chromatin remodeling (39). Moreover, we find 25 that this critical period is doubled in human cortical progenitors, which could contribute to their increased self-renewal capacities, thus uncovering a surprising link between mitochondria dynamics and human brain evolution.…”
Section: Main Textmentioning
confidence: 59%
“…For instance, intramolecular contacts between promoters and distant enhancers activate gene transcription 12 , whereas intermolecular contacts between homologous DNA sequences of replicated sister chromatids enable error-free DNA damage repair 13 . During cell cycle progression, conformational changes within and between the replicated sister chromatids shape mechanical bodies that can be segregated by the mitotic spindle [7][8][9][10][11]14 . In vertebrates, intramolecular DNA loops are dynamically formed by the Structural Maintenance of Chromosomes complex cohesin [15][16][17][18][19][20][21] within boundaries established by the CCCTC-binding factor (CTCF), thereby structuring chromosomes into topologically associating domains (TADs) [4][5][6] .…”
mentioning
confidence: 99%
“…The complex organization of vertebrate genomes has been revealed by chromosome conformation capture technology (Hi-C) [1][2][3] , which maps DNA contacts genome-wide. The development of Hi-C led to the discovery of TADs [4][5][6] and revealed how they are dynamically remodeled during the cell cycle [7][8][9][10][11] . It also allowed the elucidation of how cohesin regulates dynamic loop formation [15][16][17][18][19] , and it has been widely used to study the functional implications of chromosome conformation in various biological contexts.…”
mentioning
confidence: 99%